Development and validation of a parameter estimation methodology for two different lithium-ion batteries to optimize their performance and life cycle - Nakama V. (2021)
This paper presents four procedures developed to analyse the dependence of the discharge curve of a lithium battery on discharge current and working temperature. For this work, two models of lithium batteries have been used, whose discharge curves have different shapes. The first one, the shape of the curve describes an almost horizontal line in most of it (type 1), while in the other one, the shape of the curve describes a negative slope in most of it (type 2). Two of the developed procedures are used for discharge curves with different currents but constant temperature and the other two developed procedures are used for discharge curves with different temperatures but constant current. The information for the development of the simulations is obtained from the datasheet of the analysed lithium batteries. © 2021 Published under licence by IOP Publishing Ltd.